EFFECT OF CONCENTRATED OWNERSHIP ON AUDIT FEE STICKINESS: THE MODERATING ROLE OF FINANCIAL STATEMENT FRAUD - Dwi Nadika Suhendar Dwi Nadika Suhendar (El-Ecosy : Jurnal Ekonomi dan Keuangan Islam, 2026)
This study aims to examine the effect of concentrated ownership on audit fee stickiness with financial statement fraud as a moderating variable. The study employed a verification method with a quantitative approach. Data were collected using purposive sampling based on predetermined criteria, resulting in a sample of 50 manufacturing companies listed on the Indonesia Stock Exchange during the 2019–2023 period. With a five-year observation period, a total of 250 firm-year observations were obtained. Hypothesis testing was conducted using multiple regression analysis and Moderated Regression Analysis (MRA). The results indicate that concentrated ownership has a positive and significant effect on audit fee stickiness. Furthermore, financial statement fraud significantly and positively moderates the relationship between concentrated ownership and audit fee stickiness. These findings suggest that a higher level of concentrated ownership increases the likelihood of audit fee stickiness, and this effect becomes stronger in companies that are indicated to engage in financial statement fraud. This study contributes to the development of literature on audit fee stickiness and provides insights for future research. Future studies are recommended to apply alternative measurements for the variables and incorporate additional factors that may influence audit fee stickiness in order to obtain more comprehensive results.